Implications of e-commerce within the framework of the right to privacy (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
The digital revolution has transformed the global economy through the rise of e-commerce. In Venezuela, this expansion creates significant challenges for users' right to privacy due to extensive data collection and a loss of control over personal information, increasing the risks of vulnerability. This article analyzes the legal implications of e-commerce on the right to privacy within the Venezuelan legal framework, examining institutions such as habeas data, the right to intimacy, and internet security. Methodologically, a qualitative study was conducted using a documentary design for data collection and legal hermeneutics for interpretation. The conclusions indicate that Venezuelan legislation requires e-commerce platforms to ensure personal data protection, including informed consent for data, habeas data, collection and processing, and the right to data rectification and deletion; and its non-compliance can lead to legal liabilities and significant sanctions. Finally, we recommend modernizing and harmonizing the data protection regulatory framework, strengthening supervision and accountability for e-commerce actors, and promoting radical transparency and conscious user consent to build trust in the digital environment.
Keywords: privacy; e-commerce; data protection, data security